Combined adjuvants of poly(I:C) plus LAG‐3‐Ig improve antitumor effects of tumor‐specific T cells, preventing their exhaustion. Issue 4 (April 2016) - Kano, Yosuke; Iguchi, Takahiro; Matsui, Hiroto; Adachi, Keishi; Sakoda, Yukimi; Miyakawa, Tomoya; Doi, Shun; Hazama, Shoichi; Nagano, Hiroaki; Ueyama, Yoshiya; Tamada, Koji
Abstract : Therapeutic cancer vaccines are designed to treat cancer by boosting the endogenous immune system to fight against the cancer. In the development of clinically effective cancer vaccines, one of the most practical objectives is to identify adjuvants that are capable of optimizing the vaccine effects. In this study, we explored the potential of polyinosinic–polycytidylic acid (poly(I:C)) and LAG‐3‐Ig (soluble recombinant protein of lymphocyte activation gene‐3 [LAG‐3] extracellular domain fused with human IgG Fc region) as adjuvants for P1A tumor antigen peptide vaccine in a pre‐established P815 mouse tumor model with a transfer of tumor‐specific T cells. Whereas the use of poly(I:C) or LAG‐3‐Ig as a signal adjuvant induced a slight enhancement of P1A vaccine effects compared to incomplete Freund's adjuvant, combined treatment with poly(I:C) plus LAG‐3‐Ig remarkably potentiated antitumor effects, leading to complete rejection of pre‐established tumor and long‐term survival of mice. The potent adjuvant effects of poly(I:C) plus LAG‐3‐Ig were associated with an enhanced infiltration of T cells in the tumor tissues, and an increased proliferation and Th1‐type cytokine production of tumor‐reactive T cells. Importantly, the combined adjuvant of poly(I:C) plus LAG‐3‐Ig downregulated expressions of PD‐1, LAG‐3, and TIGIT on P1A‐specific T cells, indicating prevention of T cell exhaustion. Taken together, the results of the current study show that the combined adjuvants of poly(I:C) plus LAG‐3‐Ig with tumor peptide vaccine induce profound antitumor effects by activating tumor‐specific T cells. Abstract : This study explored a potential of poly(I:C) and LAG‐3‐Ig as adjuvants for tumor antigen peptide vaccine in the pre‐established mouse tumor model. It was found that poly(I:C) plus LAG‐3‐Ig combination as adjuvant profoundly augments therapeutic potential of tumor peptide vaccine.